VESICLES. I. Atopic dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
In this chapter atopic derrnatitis, allergie contact dermatitis, dyshidrosis and sudamina are presented. These skin diseases are all characterized by the presence of vesicles. A vesicle is an elevated lesion of about 1 millimeter in diameter, which is determined by the presence of a cavity containing fluid situated within the epidermis.